2014
DOI: 10.1080/00207543.2014.919422
|View full text |Cite
|
Sign up to set email alerts
|

An ontology framework for developing platform-independent knowledge-based engineering systems in the aerospace industry

Abstract: This paper presents the development of a novel knowledge-based engineering (KBE) framework for implementing platform-independent knowledge-enabled product design systems within the aerospace industry. The aim of the KBE framework is to strengthen the structure, reuse and portability of knowledge consumed within KBE systems in view of supporting the cost-effective and long-term preservation of knowledge within such systems. The proposed KBE framework uses an ontology-based approach for semantic knowledge manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…4) Fourth generation with main focus on strengthening modularity and reuse of engineering design ontologies to better deal with the complexity of knowledge that is required to be brought together to support the design of knowledge-based decisionmaking system. It is mainly represented by the novel knowledge-based engineering (KBE) framework which adopts best practices from previous ontology development methods along with a modeldriven architecture style to implement platformindependent knowledge-enabled product design systems, e.g., within the aerospace industry [12]. Another representative of this generation is the middleout approach suggested by Obrst et al [13], mixing aspects of top-down and bottom-up analyses.…”
Section: Ontology Development Methodologymentioning
confidence: 99%
“…4) Fourth generation with main focus on strengthening modularity and reuse of engineering design ontologies to better deal with the complexity of knowledge that is required to be brought together to support the design of knowledge-based decisionmaking system. It is mainly represented by the novel knowledge-based engineering (KBE) framework which adopts best practices from previous ontology development methods along with a modeldriven architecture style to implement platformindependent knowledge-enabled product design systems, e.g., within the aerospace industry [12]. Another representative of this generation is the middleout approach suggested by Obrst et al [13], mixing aspects of top-down and bottom-up analyses.…”
Section: Ontology Development Methodologymentioning
confidence: 99%
“…These solutions are the result of the tool evaluation in real time. This occurs as a the result of an agreement between the specialists and/or end users of the developed tool (see [18,42,49,57,59]). …”
Section: Tools For Product-service Description Based On Ontologiesmentioning
confidence: 99%
“…In [49] it is proposed a knowledge-based engineering framework which uses an approach based on an ontology for semantic knowledge management. This work adopts a modeldriven architecture from the software engineering discipline for developing platform-independent knowledge-based engineering systems in the aerospace industry.…”
Section: Tools For Product-service Description Based On Ontologiesmentioning
confidence: 99%
“…In a recent critical review of semantic technologies (Agyapong-Kodua et al 2013), it was identified that ontology frameworks often do not specify pre-development and post-development phases of ontology design activities. Most of the research undertaken within the scope of product design has mainly focused on the development and implementation of semantic technologies (Sanya and Shehab 2014). Little has been done to address the methodological frameworks used to develop ontologies in support of engineering design.…”
Section: Related Work and Research Scopementioning
confidence: 99%